The Seasonal Variations of Polycyclic Aromatic Hydrocarbon Polycyclic: A Review - Ati, Estabraq Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
With dangerous substances and their effects on health. This information is important because these substances are considered environmentally harmful and healthy. An effect of exposure to any hazardous substance depends on the dose, the exposure period, characteristics and personal habits, and whether other chemicals are present in the atmosphere. Exposure to polycyclic aromatic hydrocarbons usually occurs through inhalation of polluted air from forest fires, coal tar, or by Eating roast food, so the importance necessary to know the sequence of these compounds and how they are transported in the environment is the food chain directly to humans.